The joint effect of investors' trait scepticism and the familiarity and readability of key audit matters on the communicative value of audit reports - Xin Xu; Fengying Ye; Yasheng Chen (China Journal of Accounting Studies (CJAS), 2023)
Accounting studies have inconsistent conclusions about whether including Key Audit Matters (KAM) improves the communicative value of audit reports. We experimentally investigate the joint effect of investors' trait scepticism and the familiarity and readability of KAM on the communicative value of audit reports. Our results indicate that KAM readability enhances the communicative value of audit reports for less (more) sceptical investors when they are less (more) familiar with the issues discussed in the KAM. Additionally, using an eye-tracking device, we find that the communicative value of audit reports for nonprofessional investors depends on their visual attention paid to the KAM. These findings show that the positive effect of including KAM in audit reports is contingent on the user's trait scepticism and the content and form of the KAM. Our conclusions should be of interest to regulators and auditors when considering what and how to communicate to different financial statement users.
Keywords: 650; Key audit matters; trait scepticism; familiarity; readability; Eye-tracking; communicative value